2005
DOI: 10.1002/pola.20582
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the synthesis of poly(octadecyl acrylate) by atom transfer radical polymerization and the preparation of all comblike amphiphilic diblock copolymers

Abstract: The atom transfer radical polymerization of octadecyl acrylate (ODA) has been investigated and optimized to produce polymers with predetermined molecular weights and narrow polydispersities (Ͻ1.2). The poor solubility of the catalytic system formed with conventional ligands such as the N-(n-propyl)-2-pyridylmethanimine and 2,2Ј-bipyridine with Cu(I)Br in nonpolar reaction conditions gave poor control over molecular weight characteristics in ODA polymerizations. The use of N-(n-octyl)-2pyridylmethanimine in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 47 publications
1
69
0
Order By: Relevance
“…methyl ether methacrylate) by ATRP. [25] Moreover, Matyjaszewski et al demonstrated the synthesis of poly[(octadecyl methacrylate)-co-(ethylene glycol methyl ether methacrylate)] random and gradient copolymers by ATRP. [26] Recently, our group was interested in synthesizing gradient copolymers by batch and semi-batch nitroxidemediated radical polymerization, demonstrating the effect of the synthetic methodology on the molecular architecture.…”
Section: Full Papermentioning
confidence: 99%
“…methyl ether methacrylate) by ATRP. [25] Moreover, Matyjaszewski et al demonstrated the synthesis of poly[(octadecyl methacrylate)-co-(ethylene glycol methyl ether methacrylate)] random and gradient copolymers by ATRP. [26] Recently, our group was interested in synthesizing gradient copolymers by batch and semi-batch nitroxidemediated radical polymerization, demonstrating the effect of the synthetic methodology on the molecular architecture.…”
Section: Full Papermentioning
confidence: 99%
“…[20][21][22][23] ATRP is used to prepare block and graft copolymers with different architecture with well controlled molecular weight, and well-defined end group. [24][25][26][27][28] These block copolymers are also used for the stabilization for the gold nanoparticles. [29] Recently there are reports on the surface initiated graft copolymerization on PP.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous different acrylate monomers have also been homo-and block copolymerized by ATRP. [16][17][18][19][20] The purpose of this work is to study the controlled radical homopolymerization of 2-MEA and the possible block copolymerization with methyl methacrylate (MMA) to expand the PMEA material versatility and provide guidelines for the design of novel materials with tailor-made medical device properties.…”
Section: Introductionmentioning
confidence: 99%